The Role of Lawmaking on Norm-Setting Process - Martirosyan, Hayk (Bulletin of Yerevan University C: Jurisprudence, 2022)
The study is dedicated to revealing the peculiarities of legal organization, as well as the analysis and evaluation of the impact of legal organization in that process. Awareness and effective implementation of the legal implementation process is one of the key guarantees for improving the quality of legal acts. The practice of the Republic of Armenia in the mentioned field is lagging behind, based on which proposals are presented within the framework of this study.
Keywords: lawmaking; rulemaking; legal act; legal efficiency; security system; think tank